Implementasi E-Voting Pilkades Ciantra Berbasis Web Dengan Menggunakan Sensor Sidik Jari - Wiyanto Wiyanto (Jurnal SIGMA, 2021)
Indonesia is a democratic country in which elections for President, Governor, Regent, and Village Heads are still conducted conventionally, where there are still many shortcomings, including the problem of sending ballot logistics, old calculations and inaccurate population data with voters. who do not get their voting rights so that it is less effective in its implementation. To overcome this, especially in the selection of the Village Head, in this study a web-based electronic voting system (e-Voting) was made using a fingerprint sensor that aims to collect voters' data so that voters get their voting rights and their voting rights cannot be used by other citizens. The method used in developing this application is the waterfall method which includes the stages of needs analysis, system design, coding and testing, testing and maintenance. The result of this research is an up to date e-Voting system for counting votes, so as to minimize fraud occurring at the time of village head election. So the conclusion obtained from this study that web-based e-Voting using a fingerprint sensor can produce a quick election winner decision because it does not require tiered and accurate vote counting because citizens who choose according to the data registered. Keywords: e-Voting, fingerprint, Waterfall, PHP, Website